Empathy An Evidence-based Interdisciplinary Perspective - Kondo, Makiko (IntechOpen, 2017)
Empathy, a basic ability for understanding persons holistically, building supportive relationships, and listening attentively, includes being with suffering persons, healing, and inducing catharsis in them. Therefore, it is necessary within occupations supporting humans: education, clinical psychology, nursing, early childhood care, welfare, and medicine. Conversely, there are individual differences in empathy, and promoting its development is difficult. In this book, we use interdisciplinary approaches to empathy; for example, we discuss a new intervention, physical and cross-cultural understanding of empathy, development of empathy, and applications in general and professional education. The significance of this book is its evidence-based interdisciplinary perspective in understanding empathy.